Love Is in the AI of the BeholderArtificial Intelligence and Characters of Love - Renata E. NTELIA (E-REA)
This article examines AI in its capacity to become a companion in a love relationship, whether romantic or otherwise. It shows how AI has moved from the sphere of science fiction to become a reality in everyday life, which makes our interactions with it much more personal, and our perception of it as something human-like, if not yet human. This rightly opens discussions regarding AI behaviour and human coexistence with it. The article argues that since it is difficult, if not impossible, to exactly know how an AI thinks and as we can only discern it by its results and effects, a way to anticipate its outcome is to look at the possibilities of attachment its input entails. AI input is based on mediated human experiences found in the web—aspects of love included. As such, seeing what type of love such data can result in is a valid way of foreseeing what characteristics AI will exhibit when perceived as a love agent. The article further argues that a safe and appropriate space to explore that contingency are digital games. Using an example involving Nier: Automata, it contends that archival datasets alone, full of toxic and problematic examples of love and attachment, will give rise to equally disturbing AI-generated love characters. Instead, it proposes that games can offer a different solution by affording opportunities for cohabitation of human agents and AI, in which the AI will learn about love via playful instances of care, attachment, and attuning.